The Impact Of Marketing Mix And Service Quality On Customer Loyalty Through Customer Satisfaction In The Travel Industry - Putra, Lery Handika; Qomariah, Nurul; Sanosra, Abadi (UNIVED Press, 2026)
The need for tourism is now increasing in line with people's efforts to find tourist destinations as a way to restore their spirits. In the context of intervention at PT. Trajek Group Tour Travel, this study analyzes how the combination of marketing and service quality affects loyalty and satisfaction. The population used in this study are customers of PT. Trajek Group Tour Travel by applying a non-probability sampling method. In this study, a sample of 180 respondents was determined. The data analysis process in this study uses SEM based on Variance or Partial Least Square (SEM-PLS) with the SEM PLS Warp-PLS 7.0 application. The findings of the study indicate that the combination of marketing and service quality has a significant impact on satisfaction. The combination of marketing and service quality also affects loyalty. Satisfaction has an impact on loyalty. The combination of marketing does not have a direct influence on loyalty when considered through satisfaction. Service quality, on the other hand, influences loyalty through satisfaction.